Determinants of continuance usage intention of Fintech services (digital banking) in Malaysia: a conceptual framework - Merissa Ramindran; Hock-Ann Lee (Universal Publishers, 2024)
Purpose: This research aims to develop a conceptual framework to understand the determinants of continuance usage intention among consumers in the Malaysian banking industry. Design/methodology/approach: A cross-sectional study will evaluate Gen Y and Z in Malaysia using a quantitative approach. Data will be collected through a survey questionnaire, and PLS will be used to validate hypotheses from a sample of 300 respondents. Findings: It is expected that trust will emerge as a significant determinant of continuance usage intention, indicating that consumers who perceive a higher level of trust in fintech services are more likely to continue using digital banking platforms. Research limitations/implications: This research relies on cross-sectional data, which may limit the ability to establish causal relationships among variables. Practical implications: The findings can offer practical insights to Malaysian banks and fintech providers, helping them enhance their services based on identified determinants. Policymakers can use the findings to formulate regulations that promote trust and encourage the continued usage of fintech services in Malaysia. Originality/value: To identify factors that influence the continued usage intention of fintech services in Malaysia's banking industry, we can consider several dimensions. These include perceived usefulness, ease of use, trust and security, user experience, social influence, technology readiness, and perceived cost and value. By incorporating these dimensions into a conceptual framework, researchers can provide a comprehensive analysis of the determinants of continuance usage intention of fintech services. The framework should be adapted and refined as research progresses and new insights emerge.